Regulatory T-Cells in Pregnancy: Historical Perspective, State of the Art, and Burning Questions - Ruocco, Maria Grazia; Chaouat, Gérard; Florez, Laura; Bensussan, Armand; Klatzmann, David (Frontiers in Immunology, 2014)
In this review, we first revisit the original concept of “suppressor T cells” in pregnancy, put it in a historical perspective and then highlight the main data that licensed its resurrection and revision into the concept of “regulatory T cells” (Tregs) in pregnancy. We review the evidence for a major role of Tregs in murine and human pregnancy and discuss Treg interactions with dendritic and uterine natural killer cells, other players of maternal-fetal tolerance. Finally, we highlight what we consider as the most important questions in the field.